Association between Androgenic Hormone Levels and Left Ventricular Ejection Fraction - Gholamreza Davoodi; Alireza Amirzadegan; Mohammad Ali Boroumand; Maria Raissi Dehkordi; Ali Kazemi Saeid; Ahmad Yamini Sharif; Mehrnaz Rezvanfard; Maryam Sotoudeh Anvari (Journal of Tehran University Heart Center, 2010)
Background: Androgens have been shown to have diverse effects on the cardiovascular system. The aim of this study was to compare androgenic hormone levels in patients with different left ventricular ejection fractions (EF).